THE LIMNOGEOLOGY OF THE LAKES SAGARA AND NYAMAGOMA - Nkotagu, H. H.; Athuman, C. B. (Tanzania Journal of Engineering and Technology, 2018)
The present study focuses on the limnogeological aspects of the lakes Sagara and Nyamagoma within the Malagarasi Wetland Ecosystem. Abiotic parameters from water and sediment samples were determined during the dry and wet seasons using appropriate gears and methods. The data show variation of the abiotic parameters in both lakes from the water surface to the bottom. Lake Nyamagoma is less turbid (0.7-24 NTU) than Lake Sagara (25 to 65 NTU). The water transparency was also high at Lake Nyamagoma (0.75-1.5 m) thus supporting the observed turbidity trend. The physical chemical changes may be attributed to processes such as cooling, dissociation, dissolution, decomposition, adsorption, precipitation, cation exchange and photosynthesis. However, higher nutrient concentration was observed in the wet season than dry season with the exception of SiO 2 consequent to dilution effect by surface runoff. The mineralogical content (Kaolinite, Smectite, Illite and Quartz) of the lake sediments indicate existence of good drainage conditions at the lakes as supported by the geology of the area. It is recommended that a long-term limnogeological monitoring and evaluation be conducted so as to understand future nutrient hydrodynamics and hydrological functioning of the wetland ecosystem.